The great theorem of AA Markoff and Jean Bernoulli sequences - Khrushchev, S. (Elsevier Science Bv, 2010)
A proof of Markoff's Great Theorem on the Lagrange spectrum using continued fractions is sketched. Markoff's periods and jean Bernoulli sequence(1) are used to obtain a simple algorithm for the computation of the Lagrange spectrum below 3. (C) 2009 Elsevier B.V. All rights reserved.
International Conference on Special Functions, Information Theory and Mathematical Physics -- SEP 17-19, 2007 -- Granada, SPAIN
Keywords: Markoff's algorithm; The Lagrange spectrum; Continued fractions; Transcendental numbers